Demographic change in models of endogenous economic growth: A survey - Klaus Prettner; Alexia Prskawetz (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2010)
The purpose of this article is to identify the role of population size, population growth and population ageing in models of endogenous economic growth. While in exogenous growth models demographic variables are linked to economic prosperity mainly via the population size, the structure of the workforce, and the capital intensity of workers, endogenous growth models and their successors also allow for interrelationships between demography and technological change. However, most of the existing literature considers only the interrelationships based on population size and its growth rate and does not explicitly account for population ageing. The aim of this paper is (a) to review the role of population size and population growth in the most commonly used economic growth models (with a focus on endogenous economic growth models), (b) discuss models that also allow for population ageing, and (c) sketch out the policy implications of the most commonly used endogenous growth models and compare them to each other.
Keywords: J10; O16; O41; 330; Demographic change; endogenous R&D; economic growth; Bevölkerungsentwicklung; Alternde Bevölkerung; Wirtschaftswachstum; Neue Wachstumstheorie; Theorie